The Relationship Between Diet, Physical Activity, Rest Patterns and Fitness - Najla Salsabila; Herman Subarjah; Jajat (Journal of Physical Education Health and Sport, 2025)
Healthy lifestyle habits during adolescence, especially among junior high school students, are an important stage in supporting long-term physical development and fitness. This study aims to determine the relationship between diet, physical activity, and rest patterns with fitness focused on the cardiorespiratory endurance of junior high school students. The study used a cross-sectional design and involved 60 eighth and ninth grade students at junior high school 1 Panggarangan, Lebak Regency, Banten. Data were collected using the AFHC questionnaire for dietary patterns, the IPAQ for physical activity, the PSQI for sleep patterns, and the Beep Test to measure fitness. Data analysis includes descriptive statistics, Spearman’s correlation, and multiple linear regression. The results of the study show that diet is related to physical activity, where students with healthier eating habits tend to be more active. However, no relationship was found between diet, physical activity, and sleep patterns and fitness levels. Regression analysis also shows that these three variables do not contribute significantly to variations in student fitness. These findings indicate that cardiorespiratory fitness is influenced by factors other than the daily habits measured in this study. This study provides an initial overview of the lifestyle and fitness conditions of junior high school students, and can serve as a basis for schools and related parties to develop fitness improvement programs.